Simulation of the field aging of asphalt binders in different reclaimed asphalt pavement (RAP) materials in Hong Kong through laboratory tests. (30th December 2020) - Qian, Yu; Guo, Feng; Leng, Zhen; Zhang, Yuan; Yu, Huayang
Highlights: Different local RAP binders were collected and evaluated. Different lab aged binders were prepared using the conventional PAV method. Chemical and rheological analyses were conducted on all binders. The PAV method significantly underestimates the field aging of binder. More demanding lab aging method should be developed. Abstract: Nowadays, reclaimed asphalt pavement (RAP) are widely used in pavement construction because of its significant environmental and economic benefits. In general, the use of RAP can introduce significant reduction in emission generation, energy consumption, and construction cost. To better utilize RAP, previous studies have paid extensive efforts to accelerate and quantify aging of asphalt binders in the laboratory, with the hope to predict their long-term performance in the field. But unfortunately, the existing laboratory aging methods cannot fully represent the field conditions due to the complexity of the field aging environment, caused by various factors, such as the seasonal and local climate characteristics of the interested areas. This study aims to quantify the difference between the binder laboratory aging and field aging in subtropical climate, at Hong Kong. The chemical compositions, rheological properties, and engineering performance of the field-aged asphalt binders (FAB) from several local pavements were characterized and compared with those of the laboratory aged asphalt binders (LAB). Six FAB samples were obtained from the reclaimed asphalt pavement (RAP) mixtures which had served on urban roads at Hong Kong for different durations. In the laboratory, following the conventional approach, the rolling thin film oven test (RTFOT) followed by the (Pressure Aging Vessel (PAV) test were performed to prepare the LAB samples. The results from the dynamic shear rheometer (DSR) and Fourier transform infrared spectrometer (FTIR) tests showed that the agings of the FAB samples were significantly higher than those of the LAB samples. Specifically, the conventional laboratory aging method for asphalt binder underestimated the field aging of a four-year old stone mastic asphalt (SMA) mixture nor a five-year old dense asphalt mixture. The results of this study suggested that more demanding aging process in the laboratory be developed for better simulation of the long-term field performance of asphalt mixture.